Influence of La2O3 composition in MgO–La2O3 mixed oxide-supported Co catalysts on the hydrogen yield in glycerol steam reforming. Issue 2 (23rd January 2017) - Surendar, M.; Padmakar, D.; Lingaiah, N.; Rama Rao, K. S.; Sai Prasad, P. S.
Abstract : Partially Mg-substituted LaCoO3 perovskite is a good precursor, for the generation of cobalt nanoparticle derived under the reduction atmosphere. The La2 O2 CO3 phase formed is more efficient in removing the carbon from the cobalt active site. Abstract : MgO–La2 O3 mixed oxide (ML x ) supports with varying La2 O3 content ( x = 1, 2, 3, 4, and 5 by wt) were synthesized by a co-precipitation method. A constant composition (20 wt%) of an active metal, cobalt, was loaded on ML x supports by the wet impregnation method. The physico-chemical properties of these solids were determined by BET surface area, ICP-OES, XRD, H2 -TPR, CO2 -TPD, FT-IR, H2 -pulse chemisorption and CHN techniques. All the catalysts were evaluated for hydrogen production by vapor phase glycerol steam reforming at atmospheric pressure. Partial substitution of La in LaCoO3 with MgO has increased the reducibility of the perovskite, enhanced the dispersion of the active metal and played a vital role in carbon removal from the active site. The best catalytic activity with 100% glycerol conversion to gas products (H2, CO, CH4 and CO2 ) and a maximum hydrogen yield of 72.8% has been achieved for 20 wt% of the Co/1MgO : 3La2 O3 catalyst at 700 °C. The catalyst activity also remained stable up to 35 h on stream analysis.